ANALISIS KEKUATAN TARIK KOMPOSIT PET (Polyethylene Terephthalate) DENGAN FRAKSI VOLUME MENGGUNAKAN RESIN EPOKSI DAN SERAT KELAPA SAWIT - Tiara Dewi Nabilah Farihah (2023)
Currently, rapid changes are taking place, and everyone is striving to develop technology and products to remain relevant with the times. This study aims to utilize coconut fiber waste and PET (Polyethylene Terephthalate) in the production of composites as a waste reduction measure. Variations in the volume fraction of palm fibers in PET composites were used to determine their influence on mechanical strength, with volume fractions of 10%:90%, 20%:80%, and 30%:70%. Tensile tests were conducted according to ASTM D638 standards using the hand lay-up and vacuum methods. Based on the research data, results for tensile strength and maximum elasticity modulus were obtained. From the obtained results, it was found that the best method was the vacuum method with a 30%:70% variation, where the distribution of the composite in the sample tended to be uniform. This was evidenced by the maximum values of tensile stress and elasticity modulus, which were relatively centered and displayed a uniform curve. The vacuum method yielded a tensile strength value of 9.75464 MPa and an elasticity modulus value of 49.21222 MPa.